2011
DOI: 10.1002/mrm.22881
|View full text |Cite
|
Sign up to set email alerts
|

19F‐lanthanide complexes with increased sensitivity for 19F‐MRI: Optimization of the MR acquisition

Abstract: Fluorine-19 magnetic resonance methods offer advantages for molecular or cellular imaging in vivo due to the absence of radioactivity, lack of naturally occurring background signal, and the ability to easily combine measurements with anatomical MRI. Previous studies have shown that 19 F-MRI sensitivity is limited to millimolar concentrations by slow longitudinal relaxation. In this study, a new class of macrocyclic fluorinated lanthanide complexes is investigated where relaxation rates are significantly shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 20 publications
2
63
1
Order By: Relevance
“…6) were reported by Blamire and co-workers. 63 They used phosphonate-based 1,4,7,10-tetraazacyclododecane-1,4,7-triacetate (DO3A)-type ligands that were metalated with different lanthanide ions. Selection of the lanthanide ion and the imaging parameters were found to be key factors for using these agents for ultra-high field applications.…”
Section: Introductionmentioning
confidence: 99%
“…6) were reported by Blamire and co-workers. 63 They used phosphonate-based 1,4,7,10-tetraazacyclododecane-1,4,7-triacetate (DO3A)-type ligands that were metalated with different lanthanide ions. Selection of the lanthanide ion and the imaging parameters were found to be key factors for using these agents for ultra-high field applications.…”
Section: Introductionmentioning
confidence: 99%
“…Relaxation rates are a key factor in defining detection sensitivity. By manipulating the intramolecular distances from the lanthanide ion to the reporter group, the R 1 relaxation rate can be increased, allowing the MR sequence to be run rapidly and with high flip angle, maximizing the signal collection per unit time . R 1 for the [Dy.L 1 ] − probe was 128s −1 at 7 T, rising to 160 s −1 at 9.4 T and 185 s −1 at 11.7 T, which is slightly lower than the relaxation rate of the H‐3 protons in [TmDOTMA] (reported to be 188 s −1 at 9.4 T and 211 s −1 at 11.7 T) and substantially lower than for the H‐6 protons of TmDOTP (reported as 625 s −1 at 11.7 T) .…”
Section: Discussionmentioning
confidence: 99%
“…For simple detection of the agent in vivo, an optimized 3D gradient‐echo (3DGE) sequence was employed. Our previous work has shown that once an imaging spectral width (SW) is defined (which, with the choice of imaging matrix size determines the minimum TE), the scan should be collected at the shortest available TR under Ernst angle conditions . The minimum allowed SW for these experiments is defined by the fat‐PARASHIFT frequency difference.…”
Section: Methodsmentioning
confidence: 99%
“…This is quite analogous to optical FRET (Förster (fluorescence) resonance energy transfer), where proximity controls signal. Molecular structures are crucial to generate optimal proximity relevant to a particular lanthanide [113, 161163]. The proximity may be altered by molecular cleavage revealing enzyme activity as discussed in Section 4 [164166].…”
Section: Innovations and Enhancementsmentioning
confidence: 99%